Enterprise Portfolio Governance How Organisations Optimise Value From Their Project Portfolios - Knapp, Michael (Management for Professionals,, 2018)
This book argues that the appropriate application of the principles and practices of corporate governance to organisational portfolio, program, and projects ('3P') governance brings about highly engaged, knowledgeable, and effective governance practices, which in turn substantially improves business case success. The book addresses all three layers of portfolio, program, and project within an integrated governance framework, and it answers the fundamental questions everyone involved in 3P governance must address: • What governance structures (processes, functions, roles, responsibilities) need to be in place to ensure optimal portfolio investment outcomes? • How do I know our portfolios, as structured, will deliver expected benefits and value? • What should senior management be doing, acting in their portfolio governance roles, to deliver great portfolio outcomes? The book introduces and describes a number of important frameworks and models, designed not just for their practical application, but also to be easily comprehended by senior executives not comfortable with traditional 'project speak'.